STATE POLICY OF UZBEKISTAN IN THE DEVELOPMENT OF HUMAN CAPITAL IN THE CONDITIONS OF INNOVATIVE DEVELOPMENT (International journal of artificial intelligence, 2024)
In the effective use of labor resources, the state as an economic entity pursues and is guided by the task of achieving economic competitiveness, increasing the volume of return on investment in labor resources in the form of tax deductions, reducing social inequality, increasing social stability, reducing the crime rate, and increasing life expectancy. The state has a direct and indirect influence on the development and use of labor resources.